A rare spontaneous breast abscess due to Mycobacterium chelonae: a case report - Yayoi Sakatoku; Yoshito Okada; Yohei Takahashi (Surgical Case Reports)
Abstract Background Mycobacterium chelonae, a nontuberculous mycobacterium, commonly causes skin, soft tissue, eye, pulmonary, catheter-related, and post-surgical infections in patients with immunosuppression or trauma. M. chelonae breast infections are rare, and most cases occur following cosmetic surgery. Here, we report the first case of spontaneous breast abscess due to M. chelonae. Case presentation A 22-year-old Japanese woman presented at our hospital with swelling and pain in the right breast for the past 2 weeks without any fever. She had a 19-month-old child and stopped breastfeeding 1 month after giving birth. The patient had no history of trauma or breast surgeries, no family history of breast cancer, and was not immunocompromised. Breast ultrasonography revealed a heterogeneous hypoechoic lesion with multiple fluid-filled areas suspected to be abscesses. Dynamic contrast-enhanced magnetic resonance imaging revealed a 64 × 58 × 62 mm, ill-defined, high-signal-intensity lesion with multiple ring enhancements in the upper half of the right breast. The first diagnosis was inflammatory breast cancer or granulomatous mastitis with abscess. A core needle biopsy led to drainage of pus. Gram staining did not reveal any bacteria in the pus, but the colonies from the biopsy grew on blood and chocolate agar cultures. Mass spectrometry detected M. chelonae in these colonies. Histopathological findings revealed mastitis without malignancy. The patient's treatment regimen was oral clarithromycin (CAM) based on susceptibility. Three weeks later, although the pus had reduced, the induration in the breast did not resolve; therefore, multidrug antibiotic treatment was initiated. The patient received amikacin and imipenem infusion therapy for 2 weeks, followed by continuation of CAM. Three weeks later, tenderness in the right breast recurred with slight pus discharge. Hence, minocycline (MINO) was added to the treatment. The patient stopped CAM and MINO treatment 2 weeks later. There was no recurrence 2 years after treatment. Conclusion We report a case of M. chelonae breast infection and abscess formation in a 22-year-old Japanese woman without obvious risk factors. M. chelonae infection should be considered in cases of intractable breast abscess, even in patients without immunosuppression or trauma.